Dendrophthoe falcata (L.f) Ettingsh: A Consensus Review - Pattanayak, S.P.; Mazumder, P. Mitra; Sunita, P. (Pharmacognosy Reviews)
Herbal medicine is used by up to 80% of the population in developing countries. Dendrophthoe falcata (L.f) Ettingsh is a popular hemiparasitic plant and is used in folklore medicine for ailments including ulcers, asthma, importence, paralysis, skin diseases, menstrual troubles, pulmonary tuberculosis and wounds. Scientific evidence suggests its versatile biological functions such as it’s potentiality in immunomodulation, reducing the tumor volume, male contraception, urolithiasis and wound healing. A comprehensive account of the morphology, tissue culture, phytochemical constituents, ethnobotany and biological activities, are included in view of the recent findings of importance on the plant, Dendrophthoe falcata.
Keywords: Dendrophthoe falcata; hemiparasite plant; tissue culture; anti-tumor; review